2020
DOI: 10.1523/eneuro.0203-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Mouse Reporter Strain for the Purinergic P2X2Receptor

Abstract: The ATP-sensitive P2X 2 ionotropic receptor plays a critical role in a number of signal processes including taste and hearing, carotid body detection of hypoxia, the exercise pressor reflex and sensory transduction of mechanical stimuli in the airways and bladder. Elucidation of the role of P2X 2 has been hindered by the lack of selective tools. In particular, detection of P2X 2 using established pharmacological and biochemical techniques yields dramatically different expression patterns, particularly in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 75 publications
3
11
0
Order By: Relevance
“…Another reporter mouse line developed as a knockin mouse that is expressing Cre recombinase in a P2X2dependent fashion and subsequently crossed with a cre-sensitive tdTomato mouse line [39]. Moreover, similar to our findings, this mouse line shows reporter expression in neurons in the dentate gyrus within the hippocampus.…”
Section: Transgenic Mice As Tools To Analyze the P2r Expressionsupporting
confidence: 84%
See 1 more Smart Citation
“…Another reporter mouse line developed as a knockin mouse that is expressing Cre recombinase in a P2X2dependent fashion and subsequently crossed with a cre-sensitive tdTomato mouse line [39]. Moreover, similar to our findings, this mouse line shows reporter expression in neurons in the dentate gyrus within the hippocampus.…”
Section: Transgenic Mice As Tools To Analyze the P2r Expressionsupporting
confidence: 84%
“…In our C57BL/6 J BAC transgenic mice, we were able to demonstrate expression of the P2X2R in a subset of DRG neurons, the brain stem, the hippocampus, as well as on Purkinje neurons of the cerebellum. The expression pattern on DRG neurons and in the specified locations of the CNS, such as the hippocampus, was recently confirmed by other P2X2R transgenic mouse lines detailed below [39,40]. However, it should be reemphasized here that the weak fluorescence intensity in our P2X2R-TagRFP mouse and the therefore necessary use of anti-TagRFP immunostaining and subsequent signal amplification have precluded tracking of living cells or identifying them in sections for targeted examination, e.g., by patch-clamp electrophysiology.…”
Section: Transgenic Mice As Tools To Analyze the P2r Expressionmentioning
confidence: 65%
“…A floxed humanized P2X7 receptor knock-in mouse (P2rx7 tm1.1(P2RX7)Jde ) showed an abnormal sleep pattern upon hP2X7R deletion. (Kim et al, 2020).…”
Section: Gating Cyclementioning
confidence: 99%
“…While both the BAC transgenic Tg( P2rx4 -tdTomato)1Khakh (expressing soluble tdTomato) and the P2rx4 mCherryIN knock-in mouse (conditionally expressing mCherry-tagged P2X4) reliably reported P2X4 receptor expression ( Bertin et al, 2020 ; Xu et al, 2016 ), two BAC transgenic P2X7 receptor reporter mice (Tg(P2rx7-EGFP)FY174Gsat and Tg(RP24–114E20-P2X7-His-StrepEGFP)Ani) (expressing soluble and P2X7-fused EGFP, respectively) show highly divergent expression patterns ( Kaczmarek-Hajek et al, 2018 ), further demonstrating the need for careful characterization of mouse models, in particular those generated in high-throughput approaches. Most recently, a knock-in P2X2 Cre mouse was described, which upon crossing with Cre-sensitive reporter mice reveals P2X2 receptor expression ( Kim et al, 2020 ).…”
Section: P2x Receptor Mouse Modelsmentioning
confidence: 99%
“…Expression of these receptors has been demonstrated in rodent DRGs, but primate DRGs appear to only express P2X3 [ 48 ]. A recent study using P2X2 reporter mice showed that P2X2 expression is lower in DRGs and trigeminal ganglia than the level suggested by past studies [ 49 ].…”
Section: P2x2 and P2x3 Receptorsmentioning
confidence: 92%